PENGARUH LATIHAN MENGGUNAKAN RESISTANCE BAND TERHADAP PENINGKATAN TEKNIK PASSING ATAS BOLA VOLI SMAN 1 LUWU - Ningsi, Fitri Ayu; Nur, Suaib; Jalil, Rasyidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of training using a resistance band on the improvement of overhead pass techniques in volleyball at SMAN 1 Luwu. The research method used was an experimental method with a one-group pretest-posttest design. The research sample consisted of 20 volleyball players who were actively involved in extracurricular activities. The instrument used to measure overhead passing ability was a 60-second overhead pass skills test. The results showed an increase in the average overhead pass score from 38.20 in the pretest to 47.40 in the posttest. Normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The results of the paired sample t-test showed a t-value of 20.681, which was greater than the t-table value of 2.093, with a significance level of 0.000 (< 0.05), indicating a significant effect of resistance band training on the improvement of overhead pass techniques. Therefore, resistance band training can be an effective training method to improve overhead pass skills, particularly in strengthening arm muscles and enhancing movement coordination in volleyball players.